THE RELATIONSHIP BETWEEN TEACHERS' PERCEPTIONS TOWARDS SCHOOL CLIMATE AND THEIR DECISION-MAKING STYLES IN BAOSHAN FOREIGN LANGUAGE SCHOOL AFFILIATED WITH SHANGHAI UNIVERSITY, SHANGHAI, CHINA - CUI, FANJING; YE, YAN (Scholar: Human Sciences, 2022)
The study's main purpose was to explore the relationship between teachers' perceptions of school climate and their decision-making styles in Baoshan Foreign Language School, Affiliated with Shanghai University in Shanghai, China. The study first assessed the teachers' perception of school climate, examined the teachers' decision-making styles, and tested the relationship between these two main variables. A total of 70 full-time teachers answered questionnaires by the researchers. Mean and standard deviation were used to identify teachers' perception of school climate and decision-making style. The Pearson product correlation coefficient was used to analyze the relationship between teachers' perception of school climate and decision-making style. The results showed that the teachers in the target school had a relatively positive attitude towards the school climate. Besides, teachers' most preferred decision-making style was the group decision-making style. However, the level of perception of school climate and Autocratic decision-making styles was not significant. In addition, teachers' favorite decision-making style is the group decision-making style, followed by the consultative and autocratic styles. Pearson's correlation test showed a strong positive relationship between teachers' perceptions of school climate and group decision-making styles. The researcher discussed the findings and suggested that the stakeholders of this school should be aware of the importance of school climate and decision-making styles. Teachers should be provided a stronger professional development platform as well as various forms of communication opportunities.